Automated quantitative analysis of DCC tumor suppressor protein in ovarian cancer tissue microarray shows association with β-catenin levels and outcome in patients with epithelial ovarian cancer - Bamias, A.; Yu, Z.; Weinberger, P.M.; Markakis, S.; Kowalski, D.; Camp, R.L.; Rimm, D.L.; Dimopoulos, M.A.; Psyrri, A. (Annals of Oncology, 2006)
Background: The deleted in colorectal cancer (DCC) protein, the product of DCC tumor suppressor gene, is frequently altered in cancer. Preclinical data demonstrate that DCC regulates β-catenin levels. Here, we sought to determine the association of DCC with β-catenin protein levels, clinicopathological parameters and patient outcome in ovarian cancer using a method of in situ compartmentalized protein analysis. Methods: A tissue array composed of 150 advanced-stage ovarian cancers, treated with surgical debulking and platinum-paclitaxel (Taxol) combination chemotherapy, was constructed. For evaluation of protein expression, we used an immunofluorescence-based method of automated in situ quantitative measurement of protein analysis (AQUA). Results: One hundred and twelve patients (74%) had sufficient tissue for AQUA. The median follow-up time for the entire cohort was 33 months. Patients with low nuclear DCC expression had a 3-year progression-free survival (PFS) rate of 0% compared with 33% of those with high DCC expression (P = 0.0067). In multivariate analysis, low nuclear DCC expression level retained its prognostic significance for PFS. Between DCC and β-catenin, a significant relationship was found, where tumors with low DCC had low β-catenin and vice versa (P = 0.003). Conclusions: Low nuclear DCC levels predict for poor patient outcome inepithelial ovarian cancer. DCC may exert its antitumor function, in part, through regulation of β-catenin levels. © 2006 Oxford University Press.
Keywords: DCC; Ovarian cancer; Prognosis; β-Catenin